Screening blockers against a potassium channel with a droplet interface bilayer array. - Syeda, R; Holden, M; Hwang, W; Bayley, H (2008)
Droplet interface bilayers (DIBs) form between two lipid monolayer-encased aqueous droplets submerged in oil. Both major structural classes of membrane proteins, alpha-helix bundles and beta barrels, represented by channels and pores, respectively, spontaneously insert into DIBs when freshly expressed by cell-free transcription and translation. Electrodes embedded within the droplets allow the measurement of transmembrane ionic currents carried by individual channels and pores. On the basis of these findings, we have devised a chip-based approach for the rapid screening of blockers against ion channels. The technique is demonstrated here with the viral potassium channel, Kcv.